Epidemiology of Low Dose Aspirin Damage in the Lower Gastrointestinal Tract - Sostres, Carlos; Lanas, Angel (Current Pharmaceutical Design, 2015)
Low dose aspirin (ASA), commonly defined as the cardiovascular (CV) dose of 75 to 325 mg daily, is one of the most widely prescribed drugs in the world and the cornerstone of therapy and prophylaxis for CV disease. However, the use of low dose ASA is well known to be associated with an increased risk of different upper and lower gastrointestinal (GI) complications, such as peptic ulceration and bleeding. In the recent past, clinical research was mainly focused on ASA-related injury of the upper GI tract. However, the introduction of new endoscopic techniques, such as capsule endoscopy and balloon-assisted endoscopy for the evaluation of small bowel lesions have resulted in an increasing interest among gastroenterologists about the side effects of ASA on the large and small bowel. Furthermore, it has been demonstrated that chronic use of low dose ASA results in a variety of lesions in the lower GI tract, including multiple petechiae, erosions, ulcers, diverticular bleeding and even circumferential ulcers with stricture. The ideal treatment for small bowel injury in low dose ASA users would be withdrawal of ASA, however, this withdrawal could increase the risk of CV/cerebrovascular morbidity and mortality in high percentage of patients. Therefore, several drugs have been evaluated to identify the best choice to prevent or treat ASA-induced small bowel injury with different results. Nevertheless, further specifically designed studies with more sample size are needed to determine the best treatment for low dose ASA related GI injury.
Keywords: mortality